Monarch Butterfly Distribution and Breeding Ecology in Idaho and Washington - Waterbury, Beth; Potter, Ann; Svancara, Leona K. (Frontiers in Ecology and Evolution, 2019)
Studies of monarch butterflies (Danaus plexippus) and their milkweed (Asclepias spp.) host plants in North America have focused primarily on monarch populations ranging east of the Rocky Mountains. We report the first systematic assessment of monarch butterfly and milkweed populations in the western states of Idaho and Washington, states at the northern tier of western monarch breeding range. Results of our 2-year study (2016–2017) offer new insights into monarch breeding habitat distribution, characteristics, and threat factors in our 2 states. We documented milkweeds and breeding monarchs in all 16 climate divisions in our study area. Milkweed and breeding monarch phenologies were examined with evidence supporting 2, and possibly 3 monarch generations produced in Idaho and Washington. Key monarch breeding habitats were moist-soil sites within matrices of grasslands, wetlands, deciduous forest, and shrub-steppe supporting large, contiguous, and high-density milkweed stands. Co-occurrence of showy milkweed (A. speciosa) and swamp milkweed (A. incarnata) was an important indicator of productive monarch breeding habitat in Idaho. Nectar plants were generally limited in quantity and richness across the study area, particularly in late summer, and included frequently-used non-native, invasive species. Primary threats at milkweed sites were invasive plant species, herbicide application, and mowing, followed by secondary threats of recreational disturbance, livestock grazing, insecticide application, loss of floodplain function, and wildfire. We provide management recommendations and research needs to address ongoing stressors and knowledge gaps in Idaho and Washington with the goal of conserving monarchs and their habitats in the West.